Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian pada Produk Air Alfamart Cabang Krukut Depok - Purnama, Aan; Prakoso, Aditya Bagus (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In today’s competitive retail environment, businesses face the challenge of influencing consumer purchase decisions. The quality of products and the pricing strategy are two critical factors that can significantly affect how customers choose products in stores. Alfamart, a popular convenience store chain, offers a variety of products, including Air Alfamart, which is subject to consumer preferences and purchasing behavior. Understanding the impact of product quality and price on purchase decisions is vital for businesses to develop effective marketing strategies. This study investigates how these two factors, both individually and simultaneously, affect consumer decisions in the context of purchasing Air Alfamart at the Alfamart Krukut branch. The findings of this study provide insights for companies in designing better product offerings and pricing strategies to improve sales and customer loyalty. The research was conducted with a sample size of 80 respondents, using an associative research method with a quantitative approach. Data collection techniques included field research through observation and questionnaires, literature studies, and data analysis methods. The results indicate that product quality has a significant effect on purchase decisions, with a strong positive relationship between the two variables. This suggests that improvements in product quality lead to more favorable purchase decisions. The analysis also revealed that price significantly influences purchase decisions, with a strong relationship between the two factors. These findings highlight the importance of both product quality and price in influencing consumer choices. Furthermore, both product quality and price together have a significant simultaneous effect on purchase decisions. The combined influence of these two factors has a strong relationship with the purchasing behavior of consumers. This research implies that businesses, such as Alfamart, should prioritize product quality and pricing strategies to enhance consumer purchase decisions.